(untitled) (Medical Forum Monthly, 2020)
Objective: To determine the outcome of external fixation compared with dynamic hip screw (DHS) for the treatment of high risk elderly inter-trochanteric hip fractures according to Boyd and Graffin classification. Study Design: Randomized controlled trial Place and Duration of Study: This study was conducted at the Department of Orthopedic Surgery, Fauji Foundation Hospital, Rawalpindi from May to Nov 2019. Materials and Methods: Patients were randomly divided into two groups; patients in group A were given dynamic hip screw while patients in group B were given external fixation. The duration of surgery for each patient was recorded in minutes, starting from the time of incision till the time of closure in both groups. The study outcome was assessed in terms of surgical time Results: Out of 60 patients, 25 (41.7%) were male and 35 (58.3%) were female. The outcome (surgical time) among patients in dynamic hip screw (DHS) and external fixation was 63.90+2.57 and 35.20+2.39, which was statistically significant (p-value 0.000). Conclusion: The study concluded that external fixation has a better outcome as compared to dynamic hip screw in treatment in high-risk elderly patients with inter-trochanteric fractures.